The micro-foundations of party competition and issue ownership: the reciprocal effects of citizens’ issue salience and party attachments - Neundorf, Anja; Adams, James (Cambridge University Press, 2016)
While previous research on the reciprocal effects of citizens’ issue attitudes and their party support emphasize citizens’ issue positions, political competition revolves equally around issue salience, i.e., debates over which issue areas political parties should prioritize. Using multi-wave panel survey da¬ta from Germany and Great Britain, we analyze the reciprocal effects of citizens’ issue salience and their party support, and we conclude that citizens’ issue priorities both influence and are influenced by their party attachments, and, moreover, that these effects are linked to parties’ long-term associa¬tive issue ownership. This effect is strongest among supporters of a small issue-orientated niche par¬ty, the German Greens.